Metallochaperone UreG serves as a new target for design of urease inhibitor: A novel strategy for development of antimicrobials - Yang, Xinming; Koohi-Moghadam, Mohamad; Wang, Runming; Chang, Yuen-Yan; Woo, Patrick C. Y.; Wang, Junwen; Li, Hongyan; Sun, Hongzhe (PLOS Biology, 2018)
Author summary Urease, a metalloenzyme that catalyzes the hydrolysis of urea, plays important roles in the survival and virulence of many microbial pathogens, and has long been considered an important drug target for the development of novel antimicrobials. However, its deeply buried active site and highly specific substrate of bacterial urease make it very challenging to design effective urease inhibitors by conventional approaches. In this study, we reveal that a bismuth-based drug (colloidal bismuth subcitrate) inhibits urease activity in an unusual way. This drug binds the urease accessary protein UreG and inhibits its GTPase activity, thus perturbing nickel insertion into the apo-urease, a process called urease maturation. UreG is therefore proposed as an alternative target for the development of urease inhibitors. Using H. pylori UreG as an example, combined with virtual screening and experimental validation, we further show that several small molecules that bind and functionally disrupt UreG could indeed inhibit urease activity in bacteria and in a cell infection model and possess potent antimicrobial activity. In summary, we discovered metallochaperone UreG as a new target for the design of urease inhibitors. Such a strategy should have a broad application in the development of metalloenzyme inhibitors.